Analysis of Factors Determining Bankability Status in Indonesian Society - Reza Putri Anggraini (Management Research Studies Journal, 2026)
Economic welfare is driven by financial inclusion as an essential element, yet the effectiveness of digital technology adoption in expanding financial access still shows mixed results. This study aims to analyze the influence of financial technology penetration, internet access, and income on financial inclusion in Indonesia. Using a quantitative approach with an explanatory design, data were collected through online questionnaires from 100 respondents selected via purposive sampling. Data analysis was performed using multiple linear regression to test the relationships between variables partially and simultaneously. The results indicate that income and financial technology penetration have a positive and significant influence on financial inclusion partially. Conversely, the internet access variable does not show a statistically significant effect. This concludes that although digital infrastructure is evenly available, economic capacity and the adoption of specific digital financial services remain the primary determinants of financial accessibility. As a recommendation, strategic policies should prioritize economic empowerment programs and the development of more inclusive financial products to ensure that technology effectively bridges the financial inclusion gap.